Impact of E-Filing, Tax Knowledge and Tax Penalties on Tax Compliance in India - Navita Nathani; Silky Vigg Kushwah (Journal of International Conference Proceedings (JICP), 2019)
For so many decades, Indian government has been taking legislative and administrative measures to enhance tax compliance which in turn will increase the tax collection revenues. The current, Narendra Modi government has made tremendous efforts in formalizing the economy and making the system more transparent. Some of the measures are Goods and Services Tax (GST), Income disclosure scheme, Benami Act, digitization, and Aadhaar. All the mentioned measures have improved tax compliance in India but still, they have miles to go. Studies have been conducted to analyse and understand whether such measures taken by various governments from time to time result in more tax compliance by taxpayers. This study tries to analyze the impact of e-filing, tax knowledge and tax penalties on tax compliance by taxpayers in India. The study is casual in nature with survey method being used. The study is conducted in Delhi and NCR region and standardized questionnaires were administered among a sample of 260 tax payers. Linear multiple regression has been applied to analyze the impact of tax knowledge, penalties and e-filing on tax compliance using SPSS software. The results indicate that there is no significant impact of tax knowledge on tax compliance but the impact of tax penalties and tax e filing is significant on tax compliance. It indicates that government and tax policy makers could work on e-filing awareness programs which may result in easy and convenient filling of tax by the tax payers. By levying different kinds of tax penalties, tax payers may be motivated to pay proper and timely tax, without evading the tax amount.